Natural rubber nanocomposites: effect of carbon black/multi-walled carbon nanotubes hybrid fillers on the mechanical properties and thermal conductivity. Issue 15 (13th October 2021) - Shahamatifard, F.; Rodrigue, D.; Park, K. W.; Frikha, S.; Mighri, F.
ABSTRACT: This work presents the effect of carbon black (CB)/multiwall carbon nanotubes (MWCNT) hybrid filler system on the mechanical properties and thermal conductivity of natural rubber (NR) based nanocomposites. A 30 phr (parts per hundred of rubber) of CB nanocomposite was used as a reference for which various amounts (0.5, 1, 2 and 5 phr) of MWCNT were incorporated as a CB replacement. Scanning electron microscopy (SEM) was used to investigate the state of dispersion of the CB/MWCNT fillers inside the NR matrix, while dynamic mechanical analysis (DMA) was performed to characterize their storage and loss moduli, Payne effect and loss factor (tan δ). The scorch time (t10 ) and optimum curing time (t90 ) gradually increased with increasing MWCNT content due to the shape difference between CB and MWCNT, as well as the adsorption of curatives onto the MWCNT. Finally, due to the intrinsic properties of MWCNT and its synergy with CB, substantial improvements in thermal conductivity and mechanical properties were achieved by the substitution of 5 phr CB with MWCNT. For example, a thermal conductivity of 0.602 W/m . K was achieved, which corresponds to a 80% increase compared to the reference sample. Furthermore, a 72% and 54% increase of the modulus at 100% and 300% strain (M100 and M300) was respectively achieved, while the elongation at break decreased by only 20%.